2014
DOI: 10.12982/cmujns.2014.0036
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes in Ripened Mango and Litchi Flesh After Cryogenic Freezing and During Storage

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In addition, it was found that frozen storage for a longer time tended to lower enzyme activity. This was in agreement with the results from Tangtua, Leksawasdi, and Rattanapanone [8], which reported the gradual decrease in PPO activity during the first 4 months of mango cv. Maha Chanok storage at −24 • C.…”
Section: Color Browning Index and Ppo Activitysupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, it was found that frozen storage for a longer time tended to lower enzyme activity. This was in agreement with the results from Tangtua, Leksawasdi, and Rattanapanone [8], which reported the gradual decrease in PPO activity during the first 4 months of mango cv. Maha Chanok storage at −24 • C.…”
Section: Color Browning Index and Ppo Activitysupporting
confidence: 93%
“…RSE and R 2 were used to assess how well the models fitted the data. Drying rate (g water/g dry solid/h/m 2 ) at specific time intervals was calculated using Equation (8):…”
Section: Hot Air Dryingmentioning
confidence: 99%
See 2 more Smart Citations
“…As a non-climacteric fruit, litchi does not improve in quality after harvest (Tangtua et al, 2014), but has to ripen on the tree (Chen and Huang, 2001). Hence, an appropriate physiological maturity at harvest is crucial for proper marketable quality and shelf life (Reichel et al, 2010;Ahmed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%